Pendapatan Nasional dalam Tinjauan Ekonomi Syariah - Andriani, Desi; Masri, Rahmi Vivri; Albahi, Muhammad (Innovative: Journal Of Social Science Research, 2024)
From an Islamic economic standpoint, national income is a crucial metric for evaluating the macroeconomic circumstances of a nation. An alternate method of determining and allocating national revenue that is frequently not fairly represented by traditional methods like GDP and GNP is the Islamic economic approach. The purpose of this study is to investigate the tools utilized in Islamic economics to improve welfare and to comprehend how sharia principles are applied in the computation of national income. The literature study method is used in this investigation. The findings demonstrate that by taking into account social justice, equitable distribution, and striking a balance between material and spiritual requirements, the Islamic economic approach provides a more thorough framework. Tools like waqf, sadaqah, infaq, and zakat are crucial for enhancing welfare and attaining a more equitable distribution of wealth. A more comprehensive computation of national income is greatly aided by the Islamic economic approach. This strategy overcomes the drawbacks of traditional methods and introduces economic welfare in line with sharia norms by placing a strong emphasis on social fairness and the falah principle.